Change points: ageing and content words in large a database. - Fortier, PA; Keen, KJ; Fortier, J (Literary & Linguistic Computing, 1997)
Time-series analysis is applied to the most frequently occurring vocabulary relating to the concept of ageing in the Tresor de la Langue Francaise database. The chosen time-series method is the multiple regression model (sometimes called 'two-phase regression' or 'switching regression') of change-point analysis. The results produced by this method suggest possible interpretations of attitudes towards ageing in France during the period under study (1789-1964). The applicability of the multiple regression model of change-point analysis to literary texts is suggested.